Translation and validation of the STOP-Bang questionnaire into Slovene - Pangerc, Andrej; Petek Šter, Marija; Dolenc Grošelj, Leja (European journal of medical research, 2021)
To translate, culturally adapt and evaluate the Slovene version of the STOP-Bang questionnaire (SBQ) for use in the sleep clinic. Standard forward-backward translation and harmonisation of the Slovene translation of the SBQ were performed. Test-retest reliability was performed on a sample of healthy subjects. A cross-sectional study was performed with patients referred for a sleep study. Patients filled out the Slovene translation of the SBQ before undergoing sleep study. The validation group consisted of 256 patients, of which 237 (92.6%) were included. Mean age was 52.5 ± 14.6, 63.3% of patients were male. Obstructive sleep apnoea (OSA) (apnoea-hypopnea index (AHI) ≥ 5) was present in 69.6% of patients, of whom 22.4% had mild (AHI ≥ 5 and < 15), 21.9% moderate (AHI ≥ 15 and < 30), and 25.3% severe (AHI ≥ 30) OSA. A SBQ score of 3 had a sensitivity of 92.1 (86.9-95.7), specificity of 44.4 (32.7-56.6), PPV of 79.2 (75.5-82.4) and AUC of 0.757 (95% CI 0.692-0.823; p < 0.001) for all OSA (AHI ≥ 5). Each increase in the SBQ score was associated with an increase in the probability of OSA. This study shows that the Slovene version of the SBQ is a valid tool for evaluating the risk of OSA in a sleep clinic.